2011
DOI: 10.1103/physreve.84.021701
|View full text |Cite
|
Sign up to set email alerts
|

Filling and wetting transitions of nematic liquid crystals on sinusoidal substrates

Abstract: Close to sinusoidal substrates, simple fluids may undergo a filling transition, in which the fluid passes from a dry to a filled state, where the interface remains unbent but bound to the substrate. Increasing the surface field, the interface unbinds and a wetting transition occurs. We show that this double-transition sequence may be strongly modified in the case of ordered fluids, such as nematic liquid crystals. Depending on the preferred orientation of the nematic molecules at the structured substrate and a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 23 publications
(41 reference statements)
0
29
0
Order By: Relevance
“…In a similar way as it was obtained at nematic isotropic coexistence in Ref. [31], the interfacial tension for the LdG model has the expression…”
Section: The Modelmentioning
confidence: 71%
See 3 more Smart Citations
“…In a similar way as it was obtained at nematic isotropic coexistence in Ref. [31], the interfacial tension for the LdG model has the expression…”
Section: The Modelmentioning
confidence: 71%
“…The nematic-substrate coupling Eq. (4) has been used to study the orientational wetting phenomena on flat [33,34] and rough substrates [29][30][31]35].…”
Section: The Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Their influence is also significant in wetting phenomena. We have studied how sinusoidal patterns affect wetting of a substrate by a nematic [22] and shown that the wetting state (with the nematic-isotropic interface far from the substrate) is suppressed at high roughness being replaced by a filled state (with the interface pinned at the top of the channels) to avoid the nucleation of topological defects.…”
Section: Resultsmentioning
confidence: 99%